Seven-year outcomes in ranibizumab-treated patients in ANCHOR, MARINA, and HORIZON: a multicenter cohort study (SEVEN-UP) - Rofagha, Soraya; Bhisitkul, Robert B; Boyer, David S; Sadda, SriniVas R; Zhang, Kang (Ophthalmology (Rochester, Minn.), 2013)
To assess long-term outcomes 7 to 8 years after initiation of intensive ranibizumab therapy in exudative age-related macular degeneration (AMD) patients. Multicenter, noninterventional cohort study. Sixty-five AMD patients originally treated with ranibizumab in the phase 3 Anti-VEGF Antibody for the Treatment of Predominantly Classic Choroidal Neovascularization in AMD (ANCHOR) trial, Minimally Classic/Occult Trial of the Anti-VEGF Antibody Ranibizumab in the Treatment of Neovascular AMD (MARINA) trial, and Open-Label Extension Trial of Ranibizumab for Choroidal Neovascularization Secondary to Age-Related Macular Degeneration (HORIZON). Fourteen clinical trial sites recruited their original subjects for a return evaluation. Individual subject comparisons were obtained from the ANCHOR, MARINA, and HORIZON databases. The primary end point was percentage with best-corrected visual acuity (BCVA) of 20/70 or better; secondary outcomes included mean change in letter score compared with previous time points and anatomic results on fluorescein angiography, spectral-domain ocular coherence tomography (OCT), and fundus autofluorescence (FAF). At a mean of 7.3 years (range, 6.3-8.5 years) after entry into ANCHOR or MARINA, 37% of study eyes met the primary end point of 20/70 or better BCVA, with 23% achieving a BCVA of 20/40 or better. Thirty-seven percent of study eyes had BCVA of 20/200 or worse. Forty-three percent of study eyes had a stable or improved letter score (≥0-letter gain) compared with ANCHOR or MARINA baseline measurements, whereas 34% declined by 15 letters or more, with overall a mean decline of 8.6 letters (P<0.005). Since exit from the HORIZON study, study eyes had received a mean of 6.8 anti-vascular endothelial growth factor (VEGF) injections during the mean 3.4-year interval; a subgroup of patients who received 11 or more anti-VEGF injections had a significantly better mean gain in letter score since HORIZON exit (P<0.05). Active exudative disease was detected by spectral-domain OCT in 68% of study eyes, and 46% were receiving ongoing ocular anti-VEGF treatments. Macular atrophy was detected by FAF in 98% of eyes, with a mean area of 9.4 mm(2); the area of atrophy correlated significantly with poor visual outcome (P<0.0001). Approximately 7 years after ranibizumab therapy in the ANCHOR or MARINA trials, one third of patients demonstrated good visual outcomes, whereas another third had poor outcomes. Compared with baseline, almost half of eyes were stable, whereas one third declined by 15 letters or more. Even at this late stage in the therapeutic course, exudative AMD patients remain at risk for substantial visual decline.